Mechanisms of discourse comprehension impairment after right hemisphere brain damage: suppression in inferential ambiguity resolution. - Tompkins, Connie A.; Lehman-Blake, Margaret T.; Baumgaertner, Annette (Journal of Speech, Language & Hearing Research, 2001)
This study examined the generality of a previous finding indicating that difficulty suppressing or inhibiting context-inappropriate interpretations is an important predictor of narrative discourse comprehension for adults with right brain damage (RBD) (C. A. Tompkins, A. Baumgaertner, M. T. Lehman, & W. Fassbinder, 2000). Forty adults with RBD and 39 without brain damage listened to two-sentence stimuli and judged whether a probe word fit with the overall stimulus meaning. An ambiguous initial sentence elicited both dominant and less preferred inferences, and the second sentence resolved the ambiguity toward the initially less-likely interpretation. Probes represented the dominant inference for the first sentence and were presented at two poststimulus intervals. Probe judgment response times indicated that neither group suppressed the eventually inappropriate inferences in the time intervals studied. However, multiple regression analysis demonstrated that for individual participants with RBD, the extent of suppression from one interval to the next was a significant predictor of performance on a specialized measure of inference comprehension. The discussion evaluates these findings and identifies directions for future research. Reprinted by permission of the publisher.